Heart eyes [videorecording (DVD)] - Landon, Christopher, 1975-; Murphy, Phillip, 1982-; Kennedy, Michael, 1980-; Gooding, Mason, 1996-; Brewster, Jordana, 1980-; Sawa, Devon, 1978-; Zumbado, Gigi; Watkins, Michaela, 1971-; Holt, Olivia, 1997-; Black, Ben, (Actor); An, Yoson, 1992-; Gaylyn, James, 1954-; et al. (Sony Pictures Home Entertainment, 2025)
For the past several years, the "Heart Eyes Killer" has wreaked havoc on Valentine's Day by stalking and murdering romantic couples. This Valentine's Day, no couple is safe ...